LINC-complex mediated positioning of the vegetative nucleus is involved in calcium and ROS signaling in Arabidopsis pollen tubes - Morgan Moser; Andrew Kirkpatrick; Norman Reid Groves; Iris Meier (Nucleus, 2020)
Nuclear movement and positioning play a role in developmental processes throughout life. Nuclear movement and positioning are mediated primarily by linker of nucleoskeleton and cytoskeleton (LINC) complexes. LINC complexes are comprised of the inner nuclear membrane SUN proteins and the outer nuclear membrane (ONM) KASH proteins. In Arabidopsis pollen tubes, the vegetative nucleus (VN) maintains a fixed distance from the pollen tube tip during growth, and the VN precedes the sperm cells (SCs). In pollen tubes of wit12 and wifi, mutants deficient in the ONM component of a plant LINC complex, the SCs precede the VN during pollen tube growth and the fixed VN distance from the tip is lost. Subsequently, pollen tubes frequently fail to burst upon reception. In this study, we sought to determine if the pollen tube reception defect observed in wit12 and wifi is due to decreased sensitivity to reactive oxygen species (ROS). Here, we show that wit12 and wifi are hyposensitive to exogenous H2O2, and that this hyposensitivity is correlated with decreased proximity of the VN to the pollen tube tip. Additionally, we report the first instance of nuclear Ca2+ peaks in growing pollen tubes, which are disrupted in the wit12 mutant. In the wit12 mutant, nuclear Ca2+ peaks are reduced in response to exogenous ROS, but these peaks are not correlated with pollen tube burst. This study finds that VN proximity to the pollen tube tip is required for both response to exogenous ROS, as well as internal nuclear Ca2+ fluctuations.